Analisis Persepsi Siswa Terhadap Penerapan Role Play Dalam Kelas Berbicara Bahasa Inggris - Ludvi Ristiana Indriani; Adila Elvin Gunawan; Zaenun Nadzif; Azizah Giusty Syafanti; Khafifah Eva Gesti; Nia Pratiwi; Herningtyas Dewi Widoretno (Academica: Journal of Multidisciplinary Studies, 2023)
The English teaching in Indonesia is called Teaching English as a Foreign Language (TEFL). In terms of TEFL, there are several basic skills that should be mastered, namely listening, speaking, reading, and writing skills. Students often find it is difficult to express themselves when speaking English orally. The purpose of this research is to find out and analyze tourism students’ perception on the use of role play in English speaking class. This research uses a qualitative descriptive method. The data obtained from open-ended questionnaire as primary data to determine students’ perception on the use of role play and observation to deterimine the students’ situation when role play is implemented. The results of this study indicate that students have a positive perception on the use of role play in English speaking class. Besides that, researchers also found four benefits the implementation of role play in English speaking class, there are increasing students’ self-confidence, understanding learning material more easily, providing experience to students in the field of tourism, and providing a fun class situasion.